Adhesive wear behavior of FeB-FeMn-C coatings produced by GTAW - Yaz, Mehmet (Walter de Gruyter Gmbh, 2023)
In this paper, a high energy density beam of gas tungsten arc welding (GTAW) was employed to build a surface over low carbon steel with FeMn, FeB, and graphite powders. X-ray diffraction, optical microscopy, energy dispersive X-ray analysis, scanning electron microscopy, micro hardness tester, and adhesive wear tester were used for researching behavior of the composite coating which microstructure, hardness and dry-sliding wear. Many different carbides and borides, including Mn5C2, Fe3C, B8C, MnB, B4C, Fe3B, Fe7C3, FeB, and Mn2B, were found on the coated surfaces. The microstructure analysis shows that the shape of the graphite also depends on the FeMn-FeB-C content. The smallest weight loss was obtained from Sample S4 and the critical sliding distance was enhanced by adding graphite from 5 to 20 wt% at transition from oxidative to abrasive.
Keywords: adhesive wear; coating; FeB; FeMn; gas tungsten arc welding